Castle: The complete eighth and final season. - Fillion, Nathan, 1971-; Katic, Stana; Dever, Seamus, 1976-; Huertas, Jon; Jones, Tamala; Quinn, Molly C., 1993-; Sullivan, Susan, 1942- ([United States] : ABC Studios, 2015)
Beckett finds herself in the Captain's chair while Castle makes the leap from author to full-blown Private Investigator. The season begins with a bang as a call from a mysterious stranger puts Beckett on the run and sets off an explosive chain of events. The action gets even more exciting, and a little crazy, when Castle's daughter, Alexis, joins her father to solve the case of a lifetime.
Disc 1. XY ; XX ; PhDead ; What lies beneath ; The nose -- Disc 2. Cool boys ; The last seduction ; Mr. and Mrs. Castle ; Tone death ; Witness for the prosecution -- Disc 3. Dead red ; The blame game ; And justice for all ; The G.D.S. ; Fidelis ad mortem -- Disc 4. Heartbreaker ; Death wish ; Backstabber ; Dead again -- Disc 5. Much ado about murder ; Hell to pay ; Crossfire.
08/23/2016.
Street Smart date 8/16/16.
new dvd 2022 fall.
Nathan Fillion, Stana Katic, Seamus Dever, Jon Huertas, Tamala Jones, Molly C. Quinn, Susan Sullivan.
TV rating: TV-PG.
DVD.
Keywords: Novelists -- Drama; Crime writing -- Drama; Criminal investigation -- Drama; Television programs; Crime television programs